Common Laboratory Mice Are Susceptible to Infection with the SARS-CoV-2 Beta Variant - Kant, Ravi; Kareinen, Lauri; Smura, Teemu; Freitag, Tobias L.; Jha, Sawan Kumar; Alitalo, Kari; Meri, Seppo; Sironen, Tarja; Saksela, Kalle; Strandin, Tomas; Kipar, Anja; Vapalahti, Olli (Viruses, 2021)
Small animal models are of crucial importance for assessing COVID-19 countermeasures. Common laboratory mice would be well-suited for this purpose but are not susceptible to infection with wild-type SARS-CoV-2. However, the development of mouse-adapted virus strains has revealed key mutations in the SARS-CoV-2 spike protein that increase infectivity, and interestingly, many of these mutations are also present in naturally occurring SARS-CoV-2 variants of concern. This suggests that these variants might have the ability to infect common laboratory mice. Herein we show that the SARS-CoV-2 beta variant attains infectibility to BALB/c mice and causes pulmonary changes within 2–3 days post infection, consistent with results seen in other murine models of COVID-19, at a reasonable virus dose (2 × 105 PFU). The findings suggest that common laboratory mice can serve as the animal model of choice for testing the effectiveness of antiviral drugs and vaccines against SARS-CoV-2.